Reading Buddies: A Strategy to Increase Peer Interaction in Students With Autism. (September 2017) - Simpson, Lisa A.; Bui, Yvonne
Students with autism spectrum disorder (ASD) are often challenged by social interaction and may require substantial support to interact with peers even in inclusive settings. Having adults support students with ASD during peer interactions, however, may ostracize the student from peers without disabilities. Peer-mediated strategies are needed so that students with ASD and students without disabilities can interact in a variety of activities without undue reliance on adults. A peer-mediated approach to a shared reading activity is presented in which students without disabilities and students with ASD are taught a three-step strategy to increase social interactions around a story.